2017
DOI: 10.4149/bll_2017_020
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin: a hepatoprotective agent against radioiodine toxicity in rats

Abstract: The results of this study demonstrated that melatonin reduced the harmful effects of RAI treatment on the liver. Anti-inflammatory and antioxidant activities are likely to be involved in the mechanism underlying the radio-protective effects of melatonin (Tab. 3, Fig. 1, Ref. 30).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Rats treated under hypoxic conditions were widely used to investigate hypoxia‐induced oxidative stress in the liver, and AOPP levels in hypoxia‐treated rats could be used to evaluate protein oxidation and inflammation . In 2017, Barlas et al found that liver tissue AOPP levels were elevated in rats with radioiodine toxicity; it was determined that melatonin treatment could significantly decrease the AOPP levels compared to the radioiodine group. Moreover, Souza et al demonstrated that Pseudomonas aeruginosa infection increased the liver levels of AOPPs in experimentally infected silver catfish.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Rats treated under hypoxic conditions were widely used to investigate hypoxia‐induced oxidative stress in the liver, and AOPP levels in hypoxia‐treated rats could be used to evaluate protein oxidation and inflammation . In 2017, Barlas et al found that liver tissue AOPP levels were elevated in rats with radioiodine toxicity; it was determined that melatonin treatment could significantly decrease the AOPP levels compared to the radioiodine group. Moreover, Souza et al demonstrated that Pseudomonas aeruginosa infection increased the liver levels of AOPPs in experimentally infected silver catfish.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Renewed attention has been given to the role of melatonin in modulating behavior, immune system, and responses to stress, cancer and aging (2). Also, it has been proved that melatonin had anti-infl ammatory and antioxidant action (3). Preclinical studies have also shown that melatonin prevented short-and long-term memory impairments induced by chronic sleep deprivation and exhibited antidepressant-like actions (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…A rat model treated with intraperitoneal dexmedetomidine for preventing RAI-induced early liver damage observed that the rats treated with dexmedetomidine had lower mean scores of histopathologic parameters and lower malondialdehyde levels and higher total sulfhydryl and catalase activities than the RAI group [9]. Similarly, intraperitoneal melatonin treatment decreased the tissue advanced the oxidation of protein products and malondialdehyde levels and increase the total sulfhydryl level as well as reducing the early histopathologic damage of the liver after RAIT [34]. Moreover, montelukast had a partial radioprotector effect against the long-term liver damage at the third month of RAIT, particularly in terms of hyperemia and capsule thickening [10].…”
Section: Discussionmentioning
confidence: 99%